ATTITUDE TOWARDS WORK IN ORGANIZATION: ATTITUDE TOWARDS WORK IN ORGANIZATION - Boteva , Nina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Copyright description of some aspects of modern organization employees’ attitude towards work. Based on analysis of attitudes towards work it has been clarified why work performance of knowledgeable, skilled and experienced workers often does not meet employers’ expectations.